Classic PCOS phenotype is not associated with deficiency of endogenous vitamin D and VDR gene polymorphisms rs731236 (TaqI), rs7975232 (ApaI), rs1544410 (BsmI), rs10735810 (FokI): a case–control study of lower Silesian women. (2nd December 2015) - Jedrzejuk, Diana; Łaczmański, Łukasz; Milewicz, Andrzej; Kuliczkowska-Płaksej, Justyna; Lenarcik-Kabza, Agnieszka; Hirnle, Lidia; Zaleska-Dorobisz, Urszula; Lwow, Felicja
Abstract: Context : The role of endogenous vitamin D and vitamin D receptor (VDR) gene polymorphism in polycystic ovary syndrome (PCOS) is still controversial. Objective : The objective of this study was to investigate for the first time in women with "classic" PCOS phenotype and healthy controls the role of the serum endogenous vitamin D level and VDR gene polymorphisms in PCOS etiology. Design : Ninety-two women with "classic" PCOS phenotype and 85 controls from lower Silesia with comparable body mass index (BMI) were studied. In all women the waist circumference, android/gynoid fat deposit, parameters of lipid and glucose metabolism, testosterone, free androgen index, sex hormone binding globulin (SHBG) and vitamin D were evaluated. Also, VDR gene polymorphisms rs731236, rs7975232, rs1544410 and rs10735810 were assessed. Results : Serum vitamin D levels in both groups were comparable. Also high, comparable frequencies of hypovitaminosis and vitamin D deficiency in both groups were observed. Women with "classic" PCOS phenotype had statistically significantly higher values of all measured parameters, except serum SHBG and high-density lipoprotein (HDL)-cholesterol, which were lower. The frequency of VDR genotype polymorphism was also comparable in both groups. Conclusions : For the first time, we show that endogenous vitamin D deficiency and VDR polymorphisms are not associated with homogeneous "classic" PCOS phenotype.